Business Empowerment through Digital Marketing Strategy and Accounting Report at KWT Permata - Sumartini, Ade Ruly; Indriyani, Ni Made Vita; Putra, I Wayan Gde Yogiswara Darma (EQUATOR SINAR AKADEMIA, 2024)
Women Farmers Group (KWT) is a forum that provides opportunities for women to participate in advancing the agricultural sector. One example is KWT Permata, which is expected to provide opportunities for women in villages to channel their abilities in cultivating agricultural land. Activities held by KWT Permata, such as technical training, business management, and product marketing, aim to improve women's self-actualization in their social environment. This study will explore the role of KWT in empowering village women in Bali, especially through kombucha production, the challenges faced, and its impact on their economic and social welfare. KWT Permata has been well managed and has been touched by assistance from the Government to support the work of the KWT, but there is no or does not yet know the procedures for bookkeeping/daily records related to production, income, costs, profit and loss , so they really don't know clearly the financial conditions and positions, there is no marketing model to promote their products, the packaging is still simple and does not have a brand, and the conditions and environment of the business premises in terms of marketing are very far from the city so that the scope of product marketing is limited.